Saponins from Panax japonicus attenuate cognitive impairment in ageing rats through regulating microglial polarisation and autophagy. (1st January 2021) - Pi, Xue-Jiao; Zhao, Qing-Qing; Wang, Jin-Xin; Zhang, Xu-Lan; Yuan, Ding; Hu, Shan-Shan; He, Yu-Min; Zhang, Chang-Cheng; Zhou, Zhi-Yong; Wang, Ting
Abstract: Context: Panax japonicus is the dried rhizome of Panax japonicus C.A. Mey. (Araliaceae). Saponins from Panax japonicus (SPJ) exhibit anti-inflammatory and antioxidative effects. Objective: To explore the neuroprotective effect of SPJ on natural ageing of rat. Materials and methods: Sprague-Dawley (SD) rats 18-month-old were divided into ageing control, ageing treated with SPJ 10 or 30 mg/kg ( n = 8). Five-month-old rats were taken as the adult control ( n = 8). Rats were fed regular feed or feed containing SPJ for 4 months. Cognitive level was evaluated by Morris water maze (MWM) test. The mechanisms of SPJ's neuroprotection were evaluated by transmission electron microscope, western blot analysis, and immunofluorescence in vivo and in vitro . Results: SPJ attenuated ageing-induced cognitive impairment as indicated by elevated number of times crossing the target platform (from 1.63 to 3.5) and longer time spent in the target platform quadrant (from 1.33 to 1.98). Meanwhile, SPJ improved the morphology of microglia and synapse, and activated M2 microglia polarisation including increased hippocampus levels of CD206 (from 0.98 to 1.47) and YM-1 (from 0.67 to 1.1), and enhanced autophagy-related proteins LC3B (from 0.48 to 0.82), Beclin1 (from 0.32 to 0.51), Atg5 (from 0.22 to 0.89) whereas decreased p62 level (from 0.71 to 0.45) of ageing rats. In vitro study also showed that SPJ regulated the microglial polarisation and autophagy. Discussion and conclusions: SPJ improved cognitive deficits of ageing rats through attenuating microglial inflammation and enhancing microglial autophagy, which could be used to treat neurodegenerative disorders.